Patient-Reported Outcomes From Phase III Neoadjuvant Systemic Trial Comparing Neoadjuvant Chemotherapy With Neoadjuvant Endocrine Therapy in Pre-Menopausal Patients With Estrogen Receptor-Positive and HER2-Negative, Lymph Node-Positive Breast Cancer - Gwark, Sungchan; Ahn, Sei Hyun; Noh, Woo Chul; Lee, Eun Sook; Jung, Yongsik; Kim, Lee Su; Han, Wonshik; Nam, Seok Jin; Gong, Gyungyub; Kim, Seon-Ok; Kim, Hee Jeong (Frontiers in Oncology, 2021)
We aimed to evaluate the patient-reported outcomes (PROs) in a prospective Phase III clinical trial, comparing neoadjuvant endocrine therapy (NET) with conventional neoadjuvant chemotherapy (NCT) in patient with hormone status positive, lymph node-positive premenopausal breast cancer (NCT01622361). The patients were randomized prospectively to either 24 weeks of NCT with adriamycin plus cyclophosphamide followed by taxane, or NET with gonadotropin releasing hormone agonist and tamoxifen. The patients were examined at the surgery unit of a large tertiary care hospital with a comprehensive cancer center. PROs were assessed on the first day of the trial (Day 1, baseline) and at the end of treatment, using the breast cancer module of the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Core 23 (EORTC QLQ BR23). One hundred and eight-seven patients were randomly assigned to chemotherapy (n=95) or endocrine therapy (n=92), and 174 patients completed 24 weeks of the neoadjuvant treatment period (n=87, in each group). Baseline scores were similar between the groups. After treatment, there were no statistically significant differences in the function scales, including body image, sexual functioning, and sexual enjoyment between the groups, although the endocrine treatment group showed a significant improvement in the future perspective (hazard ratio=8.3, 95% confidence interval:1.72-18.38; P=0.021). Similarly, there were no statistically significant differences in the symptom scales between the groups, including adverse effects of systemic therapy, breast symptoms, arm symptoms, and upset about hair loss. However, although no grade 2 alopecia was reported in both groups, the NET patients reported even worse scores for “upset by hair loss” in symptom scales, compared to the NCT group. In conclusion, overall PROs were similar in both treatment groups, except for “future perspective,” which was significantly better in the NET group than in the NCT group. Unique identifier: ClinicalTrials.Gov: NCT01622361. https://clinicaltrials.gov/ct2/show/NCT01622361